The Michael addition of indoles to α, β-unsaturated ketones catalyzed by CeCl3.7H2O-NaI combination supported on silica gel - BARTOLI, Giuseppe; BARTOLACCI, Massimo; BOSCO, Marcella; FOGLIA, Gioia; GIULIANI, Arianna; MARCANTONI, Enrico; SAMBRI, Letizia; TORREGIANI, Elisabetta (Journal of organic chemistry, 2003)
Alkylation of indoles by means of the Michael addition has been the subject of a number of investigation. It is well established that regioselectivity in the additions of indoles to electron-deficient alkenes is strongly controlled by the reaction medium. In a continuation of the work on developing greener and cleaner technologies, the cerium(III) chloride heptahydrate and sodium iodide combination supported on silica gel catalyzes the alkylation of various indoles with alpha,beta-unsaturated ketones giving 3-(3-oxoalkyl)indole derivatives in good yields. The substitution on the indole nucleus occurred exclusively at the 3-position, and N-alkylation products have not been observed.